Regulation of alcohol marketing in Australia: A critical review of the Alcohol Beverages Advertising Code Scheme's new Placement Rules - Pierce, Hannah; Stafford, J.; Pettigrew, Simone; Kameron, C.; Keric, D.; Pratt, Steve (Wiley-Blackwell Publishing Ltd., 2018)
© 2018 Australasian Professional Society on Alcohol and other Drugs Introduction and Aims: Rules concerning the placement of alcohol advertisements (Placement Rules) were added to the industry-managed Alcohol Beverages Advertising Code Scheme in November 2017. This study aimed to critically review the Placement Rules and evaluate their ability to effectively regulate the placement of alcohol marketing and provide safeguards for young people in Australia. Design and Methods: An established framework for evaluating the design of an effective self-regulatory system was applied to the substantive content of the Placement Rules and associated regulatory processes. Publicly available documents, including recent Alcohol Beverages Advertising Code Scheme determinations, informed the review. Results: The objectives and key terms of the Placement Rules are inadequately defined and narrow in scope, resulting in the dismissal of almost all relevant complaints. Weaknesses identified in the regulatory processes include limited representation from external stakeholders in the development of the Placement Rules, a lack of transparency and independence in the Scheme's administration, and limited monitoring and enforcement options. Discussion and Conclusions: The Placement Rules are unlikely to reduce young people's exposure to alcohol marketing and hence fail to meet public health objectives. This review adds to the body of literature that demonstrates that industry-managed systems fail to effectively regulate alcohol marketing. Government intervention is needed if young people's wellbeing is to be prioritised.